The Impact of Bank-Specific and Macroeconomic Factors on Non-performing Loans in Sri Lankan Commercial Banks - Ekanayake, N. (DAVID PUBLISHING, 2018)
The main purpose of this study is to ascertain the effect of bank-specific and macroeconomic factors on non-performing loans in systemically and non-systemically important commercial banks in Sri Lanka over 10 year’s period from 2004 to 2013. Also, the study examines the impact of civil war that prevailed in the country for 30 years on the ex-post credit risk of the banking sector. The study employed panel data methodology to investigate the effect of bank-specific and macroeconomic factors on non-performing loans. Panel unit root test has been undertaken in order to test the stationary of the variables. Hausman test and Wald coefficient restriction test were used to select the appropriate model out of pooled, random, and fixed effect. A dummy variable panel regression model adopted to study the war effect, considering 2009 as the structural year. Findings revealed that return on assets as a proxy for bank efficiency has a significant negative influence, while non-interest income as a proxy for income diversity is positively correlated with non-performing loans of systemically important banks. Both real gross domestic products and lending rates were highly significant in both bank types. On contrary with literature, growth in bank branches is negatively correlated. Public banks do not account for higher level of non-performing loans compared to their private counterpart. Finally, it was identified that civil war had an effect on the level of non-performing loans in commercial banks. The research would have benefited if the analysis is carried out among classified types of loans offered by commercial banks. Future researchers should involve in identifying the most significant contributing loan type to the non-performing loans and its determinants. This study is one of the few studies which have investigated the causes of non-performing loans in the commercial banking industry in Sri Lanka. The analysis of civil war and its impact on non-performing loans is the first study of that nature to be conducted in the context.
Keywords: non-performing loans; credit risk; commercial banks; civil war; Sri Lanka